2021
DOI: 10.1108/cg-02-2021-0083
|View full text |Cite
|
Sign up to set email alerts
|

Managerial ability and real earnings management in family firms

Abstract: Purpose This study aims to examine the effect of managerial ability on real earnings management (hereafter REM) in family firms. Design/methodology/approach The sample consists of 864 firms-years listed in the Indonesian Stock Exchange. REM is measured by abnormal activities. Managerial ability is measured by data envelopment analysis. Data analysis uses random-effect regression analysis. Findings Family firms reduce the possibility of higher ability managers to engage in REM. Compare to non-family firms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 77 publications
(189 reference statements)
0
6
0
1
Order By: Relevance
“…Managers with higher capabilities can also use their knowledge of the company's business to deviate from standard operating activity levels and align their capabilities with REM. (Putra et al, 2021) found that managerial ability also positively affects REM.…”
Section: Theoretical Reviewmentioning
confidence: 97%
“…Managers with higher capabilities can also use their knowledge of the company's business to deviate from standard operating activity levels and align their capabilities with REM. (Putra et al, 2021) found that managerial ability also positively affects REM.…”
Section: Theoretical Reviewmentioning
confidence: 97%
“…Focusing on the monitoring function, boards are charged with monitoring management to protect shareholders’ interests and maximize shareholders’ value (Fram and Zoffer, 2005). Thus, since the quality of financial information, proxied by earnings management, is essential for protecting shareholders’ value (Dechow et al , 1996), several studies have examined the relationship between board structure and earnings management levels (Beasley and Salterio, 2001; Peasnell et al , 2005; Ebadi, 2013; Putra et al , 2021).…”
Section: Background and Hypothesismentioning
confidence: 99%
“…Hal ini dikarenakan praktik melakukan manipulasi aktivitas transaksi ini secara tidak langsung merugikan perusahaan yang dimiliknya itu sendiri, sehingga perusahaan dengan kepemilikan keluarga, seharusnya menghindari melakukan aktivitas tersebut. Namun menurut Putra et al (2021), perusahaan keluarga sebenarnya memiliki manajer yang berkemampuan tinggi dan lebih mungkin terlibat dalam manajemen laba riil, meskipun untungnya ternyata perusahaan keluarga mampu mengurangi kemungkinan tersebut.…”
Section: Kepemilikan Keluarga Dan Manajemen Labaunclassified